Rascunhos de Virgília - Nicácio, Priscila Tenório Santana (2013)
In this paper we analyze the character Virgilia, of the novel Memórias Póstumas de Brás Cubas (1881), from Machado de Assis, which is seen here as a "constellation" of text fragments capable of generating other texts without direct relationship with data from objective reality, but taking base from traces of the word Virgilia(o) itself. For this literary appraisal it must be taken into account some key categories such as "constellation", "mimesis", "intertextuality" and "metalanguage" which, when framed in a contemporary perspective and properly folded, may explain the status of a character built much more around narrator’s experimentalists and written drafts than by solutions given by the realist literature’s sociocultural context at the time. The analysis, therefore, it is possible by taking into account the foreground work’s compositional aspects, whereas considering how the narrator writes what he says is what allows us to raise the possibility of reading presented here: Virgilia as a constellational sign that spreads throughout the narrative.